Comparative Roles and Notary Responsibilities in Indonesia and Timor Leste - Carolina Da Cruz; Arif Rachman Wahyu Wicaksono; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study were 1) To explain the role of the notary and responsibilities similarity in Indonesia and Timor Leste, 2) To explain the different roles and responsibilities of notaries in Indonesia and Timor Leste. The approach I use in the preparation of the writing of this legal research is a normative legal research, as in the study of law conceived as normative regulations and as written norms created and promulgated by an agency or by the competent state authorities. This research is descriptive research that aims to paint a picture of the state of things on certain areas and at certain times. Based on the results of this study were 1) Equation notary's role and responsibilities in Indonesia and Timor Leste. In Indonesia since 2004 has passed a law concerning Notary. But in Timor Leste began in 2009 Decree-Act No. 24/2009, dated August 26, set political guidelines for Timor-Leste's notary system and assigning to the Government the responsibility to set political guidelines specified in this legal diploma. 2) The different roles and responsibilities of notaries in Indonesia and Timor Leste. On the side of this difference can describe that, it is a rule that is very effective to help the public in understanding the roles and responsibilities of notaries in force in the country, especially in Indonesia is quite effective in establishing the truth related to his profession.Keywords: Comparison; Roles; Responsibilities; Notary.